Designing highly crystalline multifunctional multicolor-luminescence nanosystem for tracking breast cancer heterogeneity. Issue 3 (7th December 2018) - Pramanik, Avijit; Begum, Salma; Rightsell, Chris; Gates, Kaelin; Zhang, Qinku; Jones, Stacy; Gao, Ye; Ruppa-Kasani, Vikram; Banerjee, Rimika; Shukla, Jayanti; Ignatius, Ashley; Sardar, Dhiraj; et al.
Abstract : Fruit based nanosystem can identify triple negative breast cancer cells. Abstract : Breast tumor heterogeneity was responsible for the death of ∼40 000 women in 2017 in the USA. Triple-negative breast cancers (TNBCs) are very aggressive, and this is the only subgroup of breast cancers that still lacks effective therapeutics. As a result, the early-stage detection of TNBCs is vital and will have huge significance in clinical practice. Driven by this need, we here report the design of highly crystalline antibody-conjugated multifunctional multicolor-luminescence nanosystems derived from the naturally available popular tropical fruits mangoes and prunes, which have the ability to detect breast cancer heterogeneity via the selective separation and accurate identification of TNBC and HER-2(+) or ER/PR(+) breast cancer cells selectively and simultaneously. The detailed synthesis and characterization of the multifunctional multicolor nanosystems derived from tropical fruits have been reported. Experimental results show that by changing the fruits multicolor-luminescence carbon dots (LCDs) can be developed, which is mainly due to the formation of highly crystalline nanodots with different heavy metal dopants and is also due to the presence of different types of surface functional group. Experimental data that are presented show that the multifunctional multicolor nanoprobe can be used for the highly selective and simultaneous capture of targeted TNBC and HER-2(+) or ER(+) breast cancer cells, and the capture efficiency can be as high as 98%. Reported data indicate that multicolor fluorescence imaging can be used for mapping heterogeneous breast cancer cells simultaneously and can distinguish targeted TNBC from non-targeted HER-2(+) or ER/PR(+) breast cancer. Our finding suggests the excellent potential of the design of multicolor nanosystems derived from natural fruits for detecting cancer heterogeneity in clinical practice.